2014
DOI: 10.1186/gb-2014-15-3-r41
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of chromatin accessibility and gene regulation by MADS-domain transcription factors in flower development

Abstract: BackgroundDevelopment of eukaryotic organisms is controlled by transcription factors that trigger specific and global changes in gene expression programs. In plants, MADS-domain transcription factors act as master regulators of developmental switches and organ specification. However, the mechanisms by which these factors dynamically regulate the expression of their target genes at different developmental stages are still poorly understood.ResultsWe characterized the relationship of chromatin accessibility, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
261
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(291 citation statements)
references
References 62 publications
9
261
2
Order By: Relevance
“…This may explain the observed removal of the H3K27me3 inhibitory histone mark and, consequently, activation of SEP3, possibly by antagonizing Polycomb Group (PcG)-mediated transcriptional repression (Smaczniak et al, 2012b). It was also shown that AP1 and SEP3 bind to enhancer sites very early during flower development and that chromatin accessibility changes only subsequently, suggesting that SEP3 acts as a pioneer transcription factor (PTF, see Glossary, Box 1) that modifies chromatin accessibility (Pajoro et al, 2014). PTFs are by definition able to bind to inaccessible, nucleosome-associated DNA sites, thus creating an open chromatin environment that is permissive for the binding of non-pioneer factors that can only bind to accessible sites (termed 'settlers' if they almost always bind to sites matching their DNA-binding motif, and 'migrants' if they are more selective, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…This may explain the observed removal of the H3K27me3 inhibitory histone mark and, consequently, activation of SEP3, possibly by antagonizing Polycomb Group (PcG)-mediated transcriptional repression (Smaczniak et al, 2012b). It was also shown that AP1 and SEP3 bind to enhancer sites very early during flower development and that chromatin accessibility changes only subsequently, suggesting that SEP3 acts as a pioneer transcription factor (PTF, see Glossary, Box 1) that modifies chromatin accessibility (Pajoro et al, 2014). PTFs are by definition able to bind to inaccessible, nucleosome-associated DNA sites, thus creating an open chromatin environment that is permissive for the binding of non-pioneer factors that can only bind to accessible sites (termed 'settlers' if they almost always bind to sites matching their DNA-binding motif, and 'migrants' if they are more selective, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…5D, bottom) that may act as repressors (Richter et al 2010;Franco-Zorrilla et al 2014). Alternatively, some trans-acting factors may bind to their binding sites regardless of chromatin status as shown in studies of A. thaliana APETALA1 and SEPALLATA3 (Pajoro et al 2014). Some TFs have also been shown to preferentially bind nucleosome-occupied regions (Teif et al 2012;Ballare et al 2013).…”
Section: Gene Expression Predictions Based On 6-mer Motifs and Nucleomentioning
confidence: 99%
“…We find that the rice AP2-like factor gene Os04g55560 is directly and negatively regulated by OsMADS1. Whereas Arabidopsis AP2 locus is bound by SEP3, it is apparently not transcriptionally regulated (Pajoro et al, 2014b). We suggest that the rice AP2-like and PLETHORA-like factors are OsMADS1 targets in an intricate gene regulatory network.…”
Section: Discussionmentioning
confidence: 97%
“…Its closest Arabidopsis ortholog is ANT, which plays important roles in floral meristems, organ patterning, and particularly ovule and gametophyte development (Krizek, 2009;Klucher et al, 1996;Yamaguchi et al, 2016). Moreover, Arabidopsis SEP3 also directly influences ANT expression in differentiating Arabidopsis floral organs (Pajoro et al, 2014b). Rice has five genes closely related to Arabidopsis AP2 (Tang et al, 2007), including SUPERNUMERARY BRACT and INDETERMINATE SPIKELET1, mutants of which indicate critical roles in rice FM specification and floret organ development (Lee and An, 2012).…”
Section: Discussionmentioning
confidence: 99%